A Semiotic Analysis of the Hosts’ Appearance and Product Displays in Live Shopping - Survey Sijabat; Margaretha Febriany Narahawarin; Nurul Istiqomah (Technium Social Sciences Journal, 2023)
This study aims to analyze the host’s appearance and product display in live shopping from a semiotic perspective. The research method used was qualitative with observation techniques and in-depth interviews. The data were obtained by observing live shopping broadcasts and conducting interviews with 30 live shopping viewers. The data were analyzed using semiotic analysis and qualitative data analysis techniques. The findings showed that the hosts’ appearance and product display in live shopping has a complex meaning that relies on the social and cultural context. The use of filters on social media and technology on smartphones influences how hosts and products are displayed in live shopping, which changes how the audience sees the products being sold. The audience’s attention and purchase decisions may be influenced by the hosts’ and the product’s appearance. Additionally, the appearance created by social media filters and smartphone technology can influence the brand image and aesthetic value of the offered products.